Penciptaan Konserto Etude Tangganada Pentatonik untuk Pembelajaran Violin dan Orkestra - Garibaldi, Pipin; Farant, Brian (Resital: Jurnal Seni Pertunjukan, 2021)
The Creation of Pentatonic Scale Etude Concerto for Violin and Orchestral Learning. This research aims to explain creating a musical work in the form of a violin etude in the form of a concerto. The concerto is arranged in a free pentatonic scale from traditional Javanese idioms: the lancaran and gangsaran rhythm. The concerto consists of one movement that contains etude material, namely learning the technique of playing the violin in a beautiful and exciting melody. The problem highlighted is students' difficulty learning etude for the violin, which is often considered complicated. In the learning process, students tend to be oriented towards violin music such as concertos, sonatas, or musical pieces (short works) compared to etude works. Therefore, it is important for creating the concerto etude to bridge the students' violin learning process, both for educative and performative dimensions. Creating the etude concerto in this traditional idiom is expected to foster student interest in learning to practice etude. The research was organized in several stages: document collection, observation, artistic, trial, and dissemination. The research/design method was taken from Reginald Smith Brindle (1986), i.e., Musical Composition and King Palmer Teach Yourself to Composed Music (1952). The method is as follows: listening to different music that is close to the research topic to find ideas, using the violin and piano to make melodic pieces, including double, triple, four-stop techniques, connecting, combining, developing synchronized melody pieces, rhythmic variations, rhythms, articulation variations, syncopations, rhythm figures, melodic decorations, harmonies, dynamic variations, and so on. The conclusion of the research on creating a concerto with one movement is more freedom to express ideas. The use of lancaran and gangsaran rhythms in a pentatonic scale to give the nuances of the Central Java region, turns out to be more nuanced with a Mandarin concerto. After being implemented, it turns out that this concerto is still quite difficult for learning violin 3.